The Insurance-Like Effect of CSR on Corporate Performance Against JCPOA. A Difference-in-Difference Approach - Yusur Faiq Abbas Sifawy; Pari Chalaki; Parviz piri (Pizhūhish/hā-yi ḥisābdārī-i mālī)
The primary objective of this research is to examine the insurance effect of corporate social responsibility (CSR) on firm performance in the context of the withdrawal from the Joint Comprehensive Plan of Action (JCPOA). In the second phase, this study investigates the effect of insurance on both short- and long-term periods. To this end, a difference-in-differences approach was employed, utilizing data from 105 companies listed on the Tehran Stock Exchange over nine years from 2015 to 2023. The results of this study indicate that the withdrawal from the JCPOA had a significant negative impact on firm performance. Regression results reveal that this negative impact was particularly pronounced in the first four years following the withdrawal and was not significant in the fifth and sixth years. Furthermore, corporate social responsibility not only has a positive effect on firm performance but also acts as an insurance tool against the negative consequences of the withdrawal from the JCPOA. This insurance effect has been confirmed with over 95% confidence in the first to third years following the withdrawal. Therefore, the presence of corporate social responsibility is essential and crucial in both the short and long term. IntroductionExisting research indicates that companies with high social responsibility gain more social capital and suffer less damage during crises. Additionally, empirical evidence has shown that increased trust in these companies can mitigate the negative effects of political shocks and serve an insurance-like role. Based on these principles, this study focuses on social responsibility as a representative of social capital and uses the difference-in-differences method to investigate the insurance-like effects of social responsibility during the withdrawal period from the JCPOA. For this purpose, data from 105 companies over the period from 2015 to 2023 were selected, and the research hypotheses were tested using Stata software.Methods & MaterialIn this applied research, multivariate regression analysis was used to examine the relationships between variables, and the methodology is retrospective. The study is also descriptive-correlational, as it assesses the relationships among several variables. Data needed to test the research hypotheses were collected from various sources, including the Kodal website, Rahvard Navin, and Hamgenin software, the activity reports of the board of directors to the general assembly, and the explanatory notes of the financial statements. The data were then classified using Excel and analyzed using Stata software. The statistical population of the research includes companies listed on the Tehran Stock Exchange between 2015 and 2023, which encompasses 105 companies.FindingThe results of the second hypothesis indicate that the withdrawal from the Joint Comprehensive Plan of Action (JCPOA) has had a significant negative impact on firm performance, while corporate social responsibility (CSR) serves as an insurance effect in mitigating these negative impacts. These findings align with existing literature, suggesting that companies with high social capital are recognized as more trustworthy, and in conditions of low public trust, investors may assign a premium valuation to these firms. According to stakeholder theory, companies that engage in positive two-way relationships with others are likely to suffer less during crises, such as the JCPOA withdrawal, because various stakeholders (including shareholders, employees, and customers) are more inclined to support such firms. Additionally, the results derived from the difference-in-differences approach reveal that the negative impact of the JCPOA withdrawal on firm performance was most pronounced in the first four years following the exit and was not significant in the subsequent years. CSR plays a crucial role and has an insurance effect in reducing the negative consequences of political shocks, such as the withdrawal from the JCPOA, on firm performance. Specifically, the negative effects of the JCPOA withdrawal on firm performance were greater in the first three years, and these negative effects diminished in the fourth year and beyond.Conclusion and ResultsThus, CSR can act as a mitigating factor during various crises, reducing harm and enhancing support for companies. This insurance effect may yield positive outcomes with over 95% confidence from the outset up to the fourth year following the JCPOA withdrawal. Therefore, the presence of CSR is vital for companies in both the short and long term. The results of this research emphasize that corporate social responsibility (CSR) can serve as a strategic tool for mitigating the negative impacts of political shocks, and companies should pay particular attention to this aspect of their activities.